Marketing Essentials - Farese Lois Schneider (McGraw Hill, 2004)
Marketing, 13/e, by Etzel, Walker and Stanton continues to be a popular, low-cost, paperback option in the Principles market. This text is thoroughly revised, completely updated, and continues to incorporate technology, and feature in-text and boxed examples that highlight global issues, technology, ethics, and applied decision making, chapter opening cases, and part-ending cases. Other marketing themes integrated throughout the text include critical and current themes such as global marketing, customer relationship management, small business and entrepreneurship. This edition features a completely new design, a new Student CD-ROM, a revised supplements package and an interactive web page.